2021
DOI: 10.1051/e3sconf/202126702048
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of MoS2Composite rGO Material in Gas Sensor

Abstract: Since the successful preparation of single-layer graphene in 2004, two-dimensional materials have gradually become one of the research hotspots in the field of materials science. However, due to the inevitable defects of intrinsic two-dimensional materials, researchers began to explore how to obtain more excellent two-dimensional materials. In this paper, the basic properties, preparation methods and application in gas sensors of MoS2/rGO composites are reviewed. This paper has a certain reference value for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Among the different types of gases, MoS 2 nanostructures are usually selective toward NH 3 gas at room temperature, which hinders their applicability as gas sensors. Although MoS 2 is a good sensing material, it has limitations, such as a low structural strength and conductivity (Huaning et al, 2021). However, few studies have shown that its selective behavior can change while forming hybrids with different materials; this can be ascribed to the charge-transferbased modulation of the channel conductivity of the gas sensor mechanism (Gottam et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Among the different types of gases, MoS 2 nanostructures are usually selective toward NH 3 gas at room temperature, which hinders their applicability as gas sensors. Although MoS 2 is a good sensing material, it has limitations, such as a low structural strength and conductivity (Huaning et al, 2021). However, few studies have shown that its selective behavior can change while forming hybrids with different materials; this can be ascribed to the charge-transferbased modulation of the channel conductivity of the gas sensor mechanism (Gottam et al, 2020).…”
Section: Introductionmentioning
confidence: 99%